Krymskij val, 9/45 neizvestnyj pamjatnik Parka Gorʹkogo - Evstratova, Marianna Vasilʹevna ca. 20./21. Jh; Koluzakov, Sergej Vladimirovič (Fond "Svjazʹ ėpoch", 2018)
The Garage Museum of Contemporary Art was preparing to relocate to Gorky Park and needed headquarters. The administration of the Central Park of Culture proposed that the museum could occupy the left half of the building at the Crimean Bridge. As architects, the museum director Anton Belov invited the FORM bureau. Starting work with a three-story building, which previously contained a large plumbing shop, the architects unexpectedly discovered that there was a big story behind the repairs of the 2000s. Discoveries made during the research, formed the basis of the book. Work on the project and work on the book were conducted in parallel. It turned out that the small building at the Crimean Bridge, which everyone has seen many times, but few can remember, is a real architectural palimpsest. It all began at the end of the 19th century, when the building of the Nikolai Bromley shipyard appeared on the bank of the Moscow River - a red-brick industrial building with a ship-repair channel connected to the river by a covered walkway. The building has been significantly rebuilt many times and managed to be a pavilion for the first All-Union Agricultural Exhibition, the club of workers of GOZNAK, one of the first sound cinemas, a bathhouse, a warehouse and a plumbing shop before becoming what it is now: the headquarters of Muzeĭ sovremennogo iskusstva "Garazh"
Istoričeskie materialy i istorija zdanija Muzeja sovremennogo iskusstva "Garaž"
Keywords: Muzej sovremennogo iskusstva "Garaž"; Geschichte 1900-2018; Gebäude; Park; Moskau; Muzeĭ sovremennogo iskusstva "Garazh" (Moscow, Russia) / Buildings / History; Factories / Remodeling for other use / Russia (Federation) / Moscow; T͡Sentralʹnyĭ park kulʹtury i otdykha im. M. Gorʹkogo (Moscow, Russia) / Buildings, structures, etc; Bildband